The Influence of Brand Image and Product Quality on Consumer Purchase Decisions: Evidence from Kopi Nur - Zefri Efdison; Anggil Nopra Lova; Dorris Yadewani; Erni Febrina Harahap (The Future of Education Journal, 2026)
This study aims to examine the influence of brand image and product quality on consumer purchase decisions at Kopi Nur. The research employed a quantitative approach with an accidental sampling technique involving 140 respondents who were consumers of Kopi Nur. Data were analyzed using multiple linear regression. The findings indicate that brand image has a positive and significant effect on consumer purchase decisions at Kopi Nur. The stronger the brand image of Kopi Nur in consumers' minds, the greater their likelihood of making a purchase decision. Product quality also has a positive and significant effect on consumer purchase decisions. The better the product quality offered—including consistent taste, premium-quality ingredients, and well-maintained serving standards—the more likely consumers are to purchase the products. Furthermore, brand image and product quality simultaneously have a significant effect on consumer purchase decisions. The study concludes that brand image and product quality are key factors that Kopi Nur should continuously strengthen to encourage consumer purchase decisions.